Kekerasan Seksual Terhadap Anak: Peran Program Underwear Rule dalam Penanganannya - Nafeeda, Aufa Raffarina; Komariah, Siti; Wulandari, Puspita (Pinisi Journal of Sociology Education Review, 2024)
Abstract: Cases of violence, especially against children, are an issue of concern in Indonesia. Data from SIMFONI-PPA of the Ministry of Women's Empowerment and Child Protection in 2023 recorded the number of violence cases reaching 26,889, with 23,601 female victims. This phenomenon is becoming increasingly serious with a significant psychological impact on victims. This research uses a literature study. The main discussion in this article is about the factors that cause sexual violence. Types of sexual violence. The impact received by victims both physically, psychologically, and social life. In addition, there are solutions to prevent sexual violence against children. Solutions to deal with child sexual abuse can use the underwear rule program.